Antifungal activity of monoterpenes against wood white-rot fungi. (January 2016) - Zhang, Zhilin; Yang, Ting; Mi, Na; Wang, Yong; Li, Guoyuan; Wang, Lihua; Xie, Yongjian
Abstract: Biodegradation of wood by fungi is a chronic problem for wood utilization. Natural products from plants have great potential as novel fungicide sources for controlling wood decay fungi as alternative to synthetic pesticides. Many plant extracts and essential oils contain monoterpenes, sesquiterpenes and aliphatic compounds. In the present study, 41 pure monoterpenes were tested for the toxicity against wood white-rot fungi, Trametes hirsuta, Schizphylhls commune, and Pycnoporus sanguineus . Results from antifungal tests revealed that β-citronellol, geraniol, carvacrol, thymol, eugenol and citral showed good antifungal activities against the three tested fungi. In addition, the carvacrol was the most toxic monoterpenes against the three tested fungi, the IC50 values against T. hirsuta, S. commune and P. sanguineus were 87.6, 53.6 and 71.7 μg ml −1, respectively. The present results indicated that carvacrol have potential to be developed as natural fungicidal agents, suggesting that further study of wood preservation treatment be warranted. Highlights: 41 monoterpenes were tested for their toxicity against white-rot fungi. Carvacrol, thymol, eugenol and citral showed good antifungal activities. The oxygenated monoterpenes exhibited higher antifungal toxicity than monoterpene hydrocarbons.